Toponymic replications in geographical and linguistic space - Caffarelli, Enzo (Geographical names in physical space, 2016)
The place names, whatever they refer to, the nature, the history, the settlement size of the referent, often do not stop to designate a single entity, but travel through time and space and that space can have a dual nature: geographical and linguistic. The place name in the geographical space moves through the duplication process and, not frequently, multiple replication, related to the migration of peoples, geomorphological and environmental issues or human settlement, commemorations and tributes, economic and touristic reasons. Instead it moves in linguistic space through two typical and often interconnected processes: lexicalization (from the proper name to the common name) with the subsequent rinomination (from the common name to the proper name) and transonimization (from a proper name to another proper name belonging to another type of onyms). This paper presents examples of Italian macro- and microtoponyms which moved in the geographic space and / or in the linguistic one both in Italy and in Italian language, and, above all, in other languages, nations and continents.